2019
DOI: 10.1080/17482631.2019.1652060
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for communication between health care professionals and parents on a neonatal ward in the presence of language barriers

Abstract: Purpose: Family-centred neonatal care views parents and child as a unit, and aims to support each family on the basis of its specific needs. Good communication can increase parents' satisfaction and reduce tension, and is necessary to create a mutual trustful relation, but is influenced by language barriers. We aimed to describe communication between neonatal health care professionals and parents in the presence of language barriers. Methods: A field study using a hermeneutic lifeworld approach, participative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Relying on third parties for interpretation of communication between nurses and caregivers however, posed challenges including delays in the delivery of essential child healthcare services. These findings support several previous studies [ 56 , 62 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…Relying on third parties for interpretation of communication between nurses and caregivers however, posed challenges including delays in the delivery of essential child healthcare services. These findings support several previous studies [ 56 , 62 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was more common to use authorized interpreters for describing a medical treatment, while information about nursing care was more often communicated via unauthorized interpreters. A study regarding healthcare professionals pointed out that interpreters were used almost exclusively in discussions with a physician regarding the child’s medical care, but very rarely in discussions with a registered nurse concerning nursing the child [24]. An exploration of this difference may be, as suggested by previous studies, that it is almost impossible to engage an interpreter for all nursing tasks, and it is often easier to ask a family member to interpret [4].…”
Section: Discussionmentioning
confidence: 99%
“…Reviews have concluded that professional interpreters can improve quality of care with fewer errors in translation, greater satisfaction among both patients and practitioners, and a greater increase in clinical outcome than ad hoc interpreters [ 3 , 16 , 17 ]. However, the role of the interpreter is not necessarily tied to whether the interpreter is professional or ad hoc [ 18 , 19 ]; patients may prefer family interpreters because they provide a different kind of support [ 17 , 18 , 20 ]. Particularly in uncomplicated situations, patients may show a preference for family members.…”
Section: Introductionmentioning
confidence: 99%